Carotid stenting in Nepal: Our experience with two cases of carotid stenosis - Rajbhandari, Pravesh; Rajbhandari, Saujanya; Neupane, Anish; Martin, Tariq; Pant, Basant (Nepal Journal of Neuroscience, 2021)
Carotid artery stenosis is one of the important risk factors for stroke. Carotid endarterectomy and carotid artery stenting are the available treatment options for managing carotid artery stenosis patients. The technology shift towards carotid artery stenting is promising due to its less invasive approach. Carotid artery stenting has become an alternative for surgically high-risk patients and high carotid lesions (lesions located at or above the second cervical vertebra). Here, we present two cases with carotid artery stenosis who were successfully treated with open-cell type carotid stent with distal filter embolic protection device.